GIMONSHI MASTERY OF FBS UNIMA JAPANESE LANGUAGE EDUCATION STUDY PROGRAM STUDENTS - Justin Wuisang (JELLT (Journal of English Language and Literature Teaching), 2022)
The research was conducted to obtain clear information about the ability of students of the Japanese Language Education Study Program to use Japanese gimonshi (question words). The Metode used in this study is a descriptive method through a quantitative approach with percentage data analysis techniques. The data collection is carried out through an ability test by providing 15 questions related to the word question in Japanese. The results of research conducted on students in the second semester of the Japanese Language Education Study Program in 2021/2022 totaling 30 people showed that many were not able to use it because the analysis value showed 46.9% which was still in the range of ≤ 50%.